Stability and failure behaviour of the vaiont slide - Hunger, Oldrich; Aaron, Jordan (Italian journal of engineering geology and environment, 2013)
<span data-sheets-value="{"1":2,"2":"The statics and dynamics of the Vaiont Slide have been studied using several models based on the theory of Limit Equilibrium, in two and three dimensions. The analyses confirmed the need to consider low bedding-parallel strength of much of the rupture surface, combined with high piezometric pressures. The role of internal strength of the rock mass is also important, to a degree that depends on the mobilization of rock mass cohesion. The slide was asymmetric and laterally constrained and is likely to have detached in two stages, separated by a surface under diagonal tension. A displacement wave analysis indicates that the slide velocity is unlikely to have exceeded 10 m/s."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">The statics and dynamics of the Vaiont Slide have been studied using several models based on the theory of Limit Equilibrium, in two and three dimensions. The analyses confirmed the need to consider low bedding-parallel strength of much of the rupture surface, combined with high piezometric pressures. The role of internal strength of the rock mass is also important, to a degree that depends on the mobilization of rock mass cohesion. The slide was asymmetric and laterally constrained and is likely to have detached in two stages, separated by a surface under diagonal tension. A displacement wave analysis indicates that the slide velocity is unlikely to have exceeded 10 m/s.